Wybrane spostrzeżenia biskupów hiszpańskich względem ustaw dotyczących tożsamości jednostki, rodziny i edukacji - Gérman Zurriarián, Roberto (Studia Europaea Gnesnensia, 2016)
The paper discusses the opinions of Spanish bishops concerning a number of selected laws passed in Spain with respect to the identity of an individual, family, and education.